An Evaluation of Curriculum Implementation of an Independent Study Subject at World Class Standard Schools in Nonthaburi Province, Thailand - Buncham, Phanudet; Thanompongchart, Phasphan; Sudrung, Jurairat (An Online Journal of Education, 2021)
This research aimed to evaluate the curriculum implementation of the independent study (IS) subject of World–Class Standard schools in Nonthaburi province, Thailand. The population was 18 World–Class Standard schools in Nonthaburi province. There were 15 informants from each school, with a total of 270 in the study, including school directors, deputy directors of academic affairs, heads of the World–Class Standard School project, and teachers of the IS subject in the 2020 academic year. The research instruments included three sets of curriculum evaluation. The data were analyzed using the calculations of percentage, mean, and standard deviation. The results show that the overall curriculum implementation was at a medium level (M = 3.03), while the evaluation result was at the fair level. Curriculum management was found to be at a mean of 3.69, and the evaluation result was at the good level. The curriculum instruction was at a mean of 2.36, and the evaluation result was at the improvement level. In the curriculum management aspect, it was found that the analysis and understanding of the curriculum and its documentation was at the highest level (M = 4.11), while the evaluation result was at the good level. In the curriculum instruction aspect, it was found that the management of learning activities and extracurricular activities was at the highest level (M = 2.88), and the evaluation result was at the fair level.